IMPROVING SCIENCE PROCESS SKILLS AND COLLABORATION ON THE LESSON REACTION RATE USING ELECTRONIC STUDENT WORKSHEET ASSISTED WITH LIVEWORKSHEETS WEBSITE - Anita Anggrahini; Rusmini Rusmini (Pendidikan Kimia FKIP Universitas Jambi, 2022)
Improving Science Process Skills And Collaboration On The Lesson On Reaction Rate Using Electronic Student Worksheet Assisted With Liveworksheets Website This study aimed to assess the feasibility of the usage of electronic student worksheets assisted with liveworksheets website to improve science process skills and collaboration on the lesson on reaction rate in terms of validity, practicality, and effectivity. The present study utilized the Analysis-Design-Development-Implementation-Evaluation (ADDIE) development model. Data collected were through interviews, questionnaires, observations, and tests. Data analysis methods used in this study comprised both qualitative and quantitative analysis techniques. Qualitative analysis techniques were carried out descriptively, while quantitative analysis techniques were performed by percentage analysis, normality test (one sample Shapiro-Wilk test), paired sample t-test, and n-gain analysis. The validity test showed an average percentage of 87% with very valid criteria. The practicality test included the results of student responses according to questionnaires and observations of student activities, and the results are an average percentage of 92% and 100%, respectively, which are categorized as very good. The effectivity test comprised the results of the pretest-posttest cognitive and science process skills. The results of the n-gains are 0,46 and 0,61, respectively, with moderate criteria, while the results of questionnaires and observation of collaboration skills are an average percentage of 94% and 83%, respectively, with very good criteria. Electronic student worksheets assisted with liveworksheets website to improve science process skills and collaboration is essential to be developed as an effort to train 21st-century skills.